IMPLEMENTATION OF VOCATIONAL LIFE SKILL EDUCATION AT SD/MI MAARIF GRABAG 2 MAGELANG - Pranti Lestari; Muna Erawati; Abdul Ghoni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Life skill education is a student’s endeavor to study the effect of life skill training on their self-esteem. This paper discusses the description of life skill education learning at MI Ma'arif Grabag 2 Magelang, describes the enabling factors in implementing life skill education at MI Ma'arif Grabag 2 Magelang, and discusses what the obstacles faced in implementing life skill education at MI Ma'arif Grabag 2 Magelang are. Type of the research is field research with a qualitative approach. Data collection techniques were interviews and documentation. The research results indicate that 1) the steps for implementing vocational life skill education at MI Ma'arif Grabag 2 Magelang, Grabag District, Magelang Regency include several aspects, such as planning, implementation, and evaluation, 2) the factors that support the success of habituation of life skills at MI Ma'arif Grabag 2 Magelang establish a cooperative relationship with stakeholders, accept new supportive opinions, facilitate adequate infrastructure like Madrasah have empty gardens that can be used to support learning vocational life skills, and 3) obstacles in implementing life skill education from internal Madrasah that need to increase teacher competencies and teacher and students’ creativity in the vocational field.